Is Surgery Needed for Diplopia after Blowout Fractures? A Clarified Algorithm to Assist Decision-making. Issue 5 (9th May 2022) - Lin, Cen-Hung; Lee, Su-Shin; Wen Lin, I; Su, Wan-Ju
Abstract : Background: Diplopia is a common symptom after blowout fractures, with an incidence of 43.6%–83%. Although there is some consensus toward surgical correction, diplopia is not always resolved by surgery. Thus, there is a clinical dilemma for surgeons with regard to performing surgery at a specific time. This review aimed to create an algorithm to support accurate and effective decision-making. Methods: We reviewed articles published on PubMed during 2013–2020 regarding orbital fractures. Articles discussing surgical treatment for blowout fractures and diplopia were included. Five reviews, six prospective cohort studies, and 33 retrospective studies were identified. After reviewing and summarizing these articles, a step-by-step algorithm was created. Results: Most authors advise immediate surgery when a patient presents with either a positive oculocardiac reflex or a "trapdoor" fracture. Early surgical correction is recommended in children to prevent profound muscle damage. In other scenarios, most authors recommend performing surgery within 2 weeks. The algorithm begins with the aspect of motility, including muscle entrapment assessed by computed tomography or limited movement of the extraocular muscle. When there is no abnormality in motility, the algorithm continues to the aspect of position. Generally, an orbital floor defect of more than 50% or 2 cm 2 or an enophthalmos of more than 2 mm is indicated for surgery. However, diplopia may also gradually resolve after improvement of periorbital edema or swelling. Conclusion: We proposed a step-by-step approach to help surgeons make effective decisions concerning surgical correction for patients suffering from blowout fractures with diplopia at different time points.